Analisis Kinerja Piutang Perusahaan Sebelum dan Masa Pandemi Covid-19 (Studi pada Sub Sektor Kesehatan yang Terdaftar di BEI) - Wafi Yahya; Widya Rizki Eka Putri; Sari Indah Oktanti Sembiring (Journal on Education, 2024)
This investigate looks at contrasts within the execution of receivables turnover in pharmaceutical segment companies some time recently and amid the Covid-19 widespread. The populace in this inquire about are pharmaceutical companies recorded on the Indonesian stock trade from 2018 to 2021. The test utilized in this investigate is the matched test t test. The comes about of this investigate are that there are contrasts in receivables turnover execution as measured by Receivable Turnover in pharmaceutical companies some time recently and amid Covid-19.